Tnfaip6 Secreted by Bone Marrow–Derived Mesenchymal Stem Cells Attenuates TNBS-Induced Colitis by Modulating Follicular Helper T Cells and Follicular Regulatory T Cells Balance in Mice - Gu, Guangli; Lv, Xiaodan; Liu, Gengfeng; Zeng, Ruizhi; Li, Shiquan; Chen, Lan; Liang, Zhaoliang; Wang, Huiqin; Lu, Fei; Zhan, Lingling; Lv, Xiaoping (Frontiers in Pharmacology, 2021)
Objective: To investigate the immunological mechanism of bone marrow–derived mesenchymal stem cells (BM-MSCs) in inflammatory bowel disease (IBD). Methods: Mice with 2,4,6-trinitrobenzene sulfonic acid (TNBS)–induced colitis were intraperitoneally injected with phosphate-buffered saline, BM-MSCs, BM-MSCs with tumor necrosis factor–induced protein 6 (Tnfaip6) knockdown mediated by RNA interference recombinant adenovirus, and BM-MSCs–infected with control adenovirus or recombinant mouse Tnfaip6. The disease activity index, weight loss, and histological scores were recorded. Serum levels of Tnfaip6 and pro- and anti-inflammatory cytokines, including interleukin (IL)-21, tumor necrosis factor-alpha (TNF-α), IL-10 were measured by enzyme-linked immunosorbent assay. The relative expression levels of these cytokines, B-cell lymphoma 6 (BCL-6) and fork-like transcription factor p3 (Foxp3) in the colon were determined by real-time quantitative PCR (RT-qPCR). BCL-6 and Foxp3 are the master regulators of follicular helper T cells (Tfh) and follicular regulatory T cells (Tfr), respectively. The infiltration of Tfh and Tfr in mesenteric lymph nodes (MLNs) and spleens was analyzed by flow cytometry. Results: Compared to the normal control group, the expression levels of BCL-6 and IL-21 in the colon, Tfh infiltration, and ratios of Tfh/Tfr in the MLNs and spleen, and the serum concentrations of IL-21 and TNF-α increased significantly in the colitis model group (p < 0.05). Intraperitoneal injection of BM-MSCs or Tnfaip6 ameliorated weight loss and clinical and histological severity of colitis, downregulated the expression of BCL-6, IL-21, and TNF-α, upregulated the expression of Foxp3, IL-10, and Tnfaip6 (p < 0.05), increased Tfr and reduced the infiltration of Tfh in the MLNs and spleen, and downregulated the Tfh/Tfr ratio (p < 0.05). On the other hand, BM-MSCs lost the therapeutic effect and immune regulatory functions on Tfh and Tfr after Tnfaip6 knockdown. Conclusion: Tfh increase in the inflamed colon, Tfh decrease and Tfr increase during the colitis remission phase, and the imbalance of the Tfh/Tfr ratio is closely related to the progression of IBD. Tnfaip6 secreted by BM-MSCs alleviates IBD by inhibiting Tfh differentiation, promoting Tfr differentiation, and improving the imbalance of Tfh/Tfr in mice.